2013
DOI: 10.1080/00185868.2013.806012
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Healthcare Volunteer Management: Insights from Volunteer Administrators

Abstract: Volunteer administrators from 105 hospitals in five states in the northeast and southern United States provided open-ended survey responses about what they perceived to be the most pressing challenges and opportunities facing healthcare volunteer management. Taken together, these 105 hospitals used a total of 39,008 volunteers and 5.3 million volunteer hours during a 12-month period between 2010 and 2011. A qualitative content analysis of administrator responses suggests that primary challenges include volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Non-profit organizations that could once rely on a steady, loyal team of volunteers are challenged by a consistent need to recruit new individuals to their volunteer ranks. Indeed, volunteers themselves lament that recruitment and selection are the biggest challenges facing non-profit organizations today (Rogers, Rogers, & Boyd, 2013). Our review of the literature shows that research has tended to focus on these ability-enhancing practices from, what we call, a motives-based, matching values, or loyalty perspective.…”
Section: Ability-enhancing Hr Practicesmentioning
confidence: 99%
“…Non-profit organizations that could once rely on a steady, loyal team of volunteers are challenged by a consistent need to recruit new individuals to their volunteer ranks. Indeed, volunteers themselves lament that recruitment and selection are the biggest challenges facing non-profit organizations today (Rogers, Rogers, & Boyd, 2013). Our review of the literature shows that research has tended to focus on these ability-enhancing practices from, what we call, a motives-based, matching values, or loyalty perspective.…”
Section: Ability-enhancing Hr Practicesmentioning
confidence: 99%
“…To keep the survey length and time to a minimum, demographic information was limited to questions about respondent's tenure at their current organization as well as the field or service domain in which the organization operates. As expected, given the nature of the listservs through which the survey was distributed (a limitation of the survey, asdiscussed in more detail later), and the fact that certain sectors (e.g., healthcare and health services) are more likely to have well-established volunteer programs with professional volunteer administrators (Rogers, Rogers, & Boyd, 2013), the majority of respondents (74%) indicated that their organization was in healthcare or health services. The remaining respondents indicated that their organization operated in human services (6%), education (3%), arts and culture (6%), or other (11%).…”
Section: Participant Demographics: Tenure and Organizational Fieldmentioning
confidence: 61%
“…Other reasons mentioned for not participating in volunteer work were: lack of opportunities, lack of information and overloaded academic activities. Studies like that of Rogers, Rogers and Boyd (2013) support the idea of volunteer management in healthcare services, which can be done by expanding volunteering recruitment pools and improving logistics to support volunteers and best match competencies with the roles to be fulfilled. /dx.doi.org/10.15405/epsbs.2019.02.19 Corresponding Author: Roxana Bejan-Muresan Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 160 Similar to this result, there are medical studies supporting the idea that gaining professional experience by volunteering might stimulate student motivation (Chen, Sheu, Sullivan, Ten Cate, & Teherani, 2014;Schutte et al, 2017).…”
Section: Motives For Volunteeringmentioning
confidence: 99%